Medicinal and aromatic plants: Healthcare and industrial applications – a book review - Singhal, Parul; Maheshwari, Amisha; Semwal, Prabhakar (Ethnobotany Research and Applications, 2025)
Medicinal and Aromatic Plants – Healthcare and Industrial Applications. Tariq Aftab and Khalid Rehman Hakeem (Eds). Springer Nature Switzerland AG 2021. eBook ISBN: 978-3-030-58975-2; doi: https://doi.org/10.1007/978-3-030-58975-2 As highlighted in Medicinal and Aromatic Plants – Healthcare and Industrial Applications, edited by Tariq Aftab and Khalid Rehman Hakeem (2021), this book presents the various applications of medicinal and aromatic plants in different sectors including healthcare, industry and pharmaceutical (Fig. 1). This compilation provides valuable insights for students and researchers who are working on medicinal and aromatic plants.